Prototype Design Collection Series 4 - Rusli, Ahmad Najmie (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This digital book on Prototype Design Collection Series 4 (PDC Series 4) is published as a reference design for mechanical engineering students. The designs presented experience a few phases of analysis before fabrication of prototype. Each project summarises the project description, prototype, figures, and design parameter. The design products vary in tools or equipment for household, workshop, entrepreneur, etc. Suggested material and detail of prototype dimension are also mentioned in this book. It is hoped that this book will assist the students to have more ideas on innovation design products in the future.